Private Hospital Legal Entity Liability for Negligence in Health Services Based on Doctrine Corporate Negligence - Seska Pukul (AIBPM Publisher, 2021)
This study aims to examine the nature of the doctrine of Corporate Negligence for negligence in health services in private hospitals, explain the legal arrangements for negligence in health services in private hospitals and find forms of responsibility for private hospitals for negligence in health services based on the concept of corporate responsibility. Regarding the responsibility of the Hospital for negligence in health services as regulated in Article 46 of Law number 44 of 2009, concerning Hospitals, it is not explained in detail who can represent the Hospital to be legally responsible for the negligence and loss as intended. This research used normative legal research and the literature study was carried out using a series of documentation studies by collecting, reading, studying, making notes, and quotes and reviewing library materials that are related to the problems under discussion. Based on the results, The point of the doctrine Corporate Negligence is to maintain safe and adequate facilities and equipment for patients, to select and retain only competent doctors, to supervise all those who practice medicine within the Hospital to treat patients and to formulate, adopt, and enforce adequate rules and policies for the treatment of patients.